THE CRITICAL APPROACH AND THE PROBLEMATIC OF TERMINOLOGICAL DIVERSITY - Berdi, Saliha ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2020)
The terminological system determines what knowledge is, and if this limitation is ignored, tracing its effects and representing its possible perceptions is an impossible multiplication, because the systematic practice, even if it represents the essence of the critical lesson, the terminological system achieves the dynamism and dynamism of this practice from the theoretical and procedural standpoint, in light of This importance imposes idiomatic experimentation in the system of critical discourse itself as a problem that will overturn the scales, if convincing solutions are achieved, because the change that follows the system of monetary convention imposes an amendment in the formation of the systematic system, and the reliable reading perception in the approach to the text, and if it is These recent top concerns of critical thinking, the accountability of pluralism within the terminological approach Mahith concerned Bnsagh, has become the other of the challenges of this thinking, and exciting questions controversial.